Analysis of Technology for Mitigation of The Effects of Climate Change on Buildings in Kaloum (Guinea-Conakry) (International Journal of Engineering and Computer Science, 2024)
Information and communications technologies (ICTs) can, in a number of ways, contribute to meeting the requirements of the three main pillars of the Bali Action Plan, which was developed at the thirteenth Conference of the Parties in December 2007. These pillars concern enhanced action on adaptation, concerted action to reduce greenhouse gas (GHG) emissions and climate change mitigation measures. ICTs can support these actions and address the climate change issues that all countries (and particularly developing countries) face. ICTs can also be used to mitigate the influence of other sectors on GHG emissions and to help countries adapt to climate change.